13. CURRENT SITUATION OF CONTINUING MEDICAL EDUCATION FOR PHYSICIANS AT BINH DUONG PROVINCIAL GENERAL HOSPITAL IN 2023 (Tạp chí Y học Cộng đồng, 2025)
Objective: To assess the current status of continuing medical education (CME) for physicians at Binh Duong General Hospital during the first nine months of 2023.Subjects and methods: A cross-sectional descriptive study was conducted on 218 physicians who voluntarily participated by completing a self-administered, anonymous questionnaire.Results: The proportion of physicians assigned to CME activities was 90.4%. Physicians with a professional practice certificate were more likely to participate (93.3%) than those without (81.8%) (p < 0.05). The average appropriateness score for the training courses was 3.82 out of 5, with 10.6% rating them as very appropriate and 59.6% as applicable. Physicians holding a license to practice were 3.1 times more likely to participate in CME compared to those without a license.Conclusion: The hospital's CME activities demonstrated high physician participation. However, it is necessary to enhance communication about CME regulations and continue improving the quality of training programs in the future.
Keywords: Physician; general hospital; Binh Duong; continuing medical education; current status.